1995
DOI: 10.1002/jemt.1070310511
|View full text |Cite
|
Sign up to set email alerts
|

Differential connexin distribution accommodates cardiac function in different species

Abstract: Using immunohistochemical staining, the distribution of connexin40 (Cx40) and connexin43 (Cx43) was studied in rat, guinea pig, porcine, bovine and human hearts. These species display differences in the degree of morphological differentiation of the conduction system. This study was performed in the anticipation that comparison of the distributions of Cx40 and Cx43 in young and adult specimens may provide clues as to the physiological role of connexins in the heart. To a large extent, the distribution patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
76
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(78 citation statements)
references
References 27 publications
2
76
0
Order By: Relevance
“…In the atrioventricular bundle, as well as in the atrioventricular node, atrioventricular canal, and lower interatrial septum, they measured low conduction velocities compared with the velocities in the atrial auricle and ventricle. In line with this, the gap junctional proteins Cx40 and Cx43 are generally found to be absent from the atrioventricular bundle and proximal part of the bundle branches in fetal and neonatal mammalian hearts (311). In adult hearts of both mouse and human, the atrioventricular bundle is fast conducting (128,161).…”
Section: E Fate Of the Primary Ringmentioning
confidence: 66%
“…In the atrioventricular bundle, as well as in the atrioventricular node, atrioventricular canal, and lower interatrial septum, they measured low conduction velocities compared with the velocities in the atrial auricle and ventricle. In line with this, the gap junctional proteins Cx40 and Cx43 are generally found to be absent from the atrioventricular bundle and proximal part of the bundle branches in fetal and neonatal mammalian hearts (311). In adult hearts of both mouse and human, the atrioventricular bundle is fast conducting (128,161).…”
Section: E Fate Of the Primary Ringmentioning
confidence: 66%
“…Previous reports described CX40 as a marker of the proximal ventricular conduction system (VCS) in several mammalian species (Gourdie et al, 1993;Gros et al, 1994Van Kempen et al, 1995). In adult mouse and rat hearts CX40 was shown to be expressed in the His bundle and the bundle branches (Gros et al, 1994.…”
Section: Distribution Of Cx40 In the Conduction Systemmentioning
confidence: 98%
“…In addition, in the adult rat and mouse, CX43 is also absent from the ventricular conduction tissue, i.e., the His bundle and the proximal part of the bundle branches (Van Kempen et al, 1991;Gourdie et al, 1992). Interestingly, CX40 distribution studies (Gourdie et al, 1993;Gros et al, 1994Gros et al, , 1995Van Kempen et al, 1995) showed that CX40 has a more restricted distribution than CX43 in adult mammalian hearts. These authors demonstrated that (2x40 is expressed not only in atria (depending on the species) but also in ventricular conduction system myocytes.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] The structure of the specific conduction system in the right and left septal wall of the human 11 and dog heart 12 is similar to that of the mouse. 13 The generation of connexin knockout mice has revealed the importance of the respective gap junction isoforms for propagation of the electrical impulse through the conduction system.…”
mentioning
confidence: 99%